“Obtención y caracterización del almidón de papa aérea (discorea bulbifera L.)” - Dávila Rivera,Arbel (2000)
The present paper of investigation searchs the use of rustic cultures still unexploited, like is the case of air potato, sachapapa o ñame (Dioscorea bulbifera L.); which find distributed all around region San Martin and part of Loreto (province Alto Amazonas), in cultivated or rustic form, and moreover they do not require more urgent in soils and that can develope into acid soils, shapumbals and fields exploited by the man; the study comprehended severa! analysis: raw material, starch and necessary physic-chemical properties. It used as raw material the air bulbs, that they did weigh 26 to 567.3 gr., with a average weight 147.2 gr., average measures of size were 9 cm. large , 6.04 cm. wide and 4.47 cm. height or thickness; the majority of studied air bulbs got kidney-shaped, hepatic and polyhedric form. The analysis proximal chemistry of fresh bulbs reports a content of 64.996% moisture, 1.388% protein, 0.35% fat, 1.04% ash , 0.873% fiber and 31.3530% total carbohydrates, which were 25.6202% starch, 3.2615% reductor sugars, and 2.4713% another carbohydrates. The starch fraction reached a extraction percentage of 20.47%, proximal chemistry composition of air potato starch (Dioscorea bulbifera L.), was 13.46% moisture, 0.22% protein, 0.13% fat, 0.214% ash, 0.58% fiber, 85.918% total carbohydrates, which were - 19 - 0.1296% reductor sugars and 85. 7884% starch humidity base. Other analysis reached were 0.0326% total acidity expressed in sulphur acid percentage, a pH 6.47, calcium oxalate content 74.21 mg/100 grand content of calcium 23.19 mg/100 gr. The studied starch granules present different geometrical forms but great majority got triangular shapes with round or oval points, size of granules fluctuates in the range 8 to 75 μm large, with a average diameter sized by number 35.73 μm, that it is in the range 21 to 40 μm and average diameter sized by weight 45.89 μm. The analysis of starch physical characteristics of air potato (Dioscorea bulbifera L.), show a low percentage of solubility 24.03% and swelling power 25.03 at 95ºC. The iodine affinity records a value 4.53, that indicates a high content of amylose. The temperature of gelatinization is in the range 72 to 95ºC, considered as slow gelatinization. The microbiological analysis record values very under allowed limits for starchs, that demonstrates it did work with good conditions of hygiene and cleanliness in the process of air potato starch (Dioscorea bulbifera L.) extraction.